Validated transport conditions maintain the quality of washed red blood cells. Issue 9 (16th August 2022) - Baker, Steven Andrew; Wong, Lisa Kanata; Wieland, Rebekah; Bulterys, Philip; Allard, Libby; Nguyen, Lang; Quach, Thinh; Nguyen, AnhThu; Chaesuh, Eunkyong; Cheng, Phil; Bowen, Raffick; Virk, Mrigender
Abstract: Background: Washing red blood cell (RBC) units prior to transfusion is indicated for certain patients. In the United States, units stored at 1°C–6°C or transported at 1°C–10°C are available for issue up to 24 h, if not used immediately. The washing procedure commonly utilizes room temperature saline resulting in units starting out above the allowed temperature range. This leads to wastage if units are issued and returned too quickly before having a chance to equilibrate in a transport cooler. Study Design and Methods: Here we performed an experimental study of washed RBC quality comparing "ideal" storage conditions in a blood bank refrigerator to a "real‐world" simulation of unit transport, including holding in a transport cooler. Twelve RBC units were washed and allocated evenly into either condition. Results: Measurements at 0, 1, 3, 6, 12, and 24 h post‐washing revealed that placement in a transport cooler was associated with higher unit temperature prior to 12 h ( p = .013) with a maximum difference of 9.3°C. Despite this difference, several measures of unit quality including extracellular potassium, pH, lactate, and free hemoglobin were indistinguishable between conditions ( p = .382, .224, .286, .691, respectively). We selected half of the tested units from our irradiated inventory and confirmed increased potassium leak ( p < .001) and accumulation of free hemoglobin ( p = .012) in irradiated units. Discussion: Washed units stored under approved transport conditions are acceptable to return to inventory up to 24 h after washing and we provide a prediction interval‐based temperature threshold for rejecting these units, permitting reduced waste.